Reciprocal fit concept in mission statement research - Toh, Seong-Yuen *; Cheok, Jason *; Mughal, S. A. (2019)
There is a stalemate in mission-performance research. While past studies focus on strategic alignment, recent studies attempt to move the mission-performance research forward using the reciprocal fit concept. This concept provides explanatory power in predicting performance of the firm. However, there is a lack of research into the reciprocal fit concept. The concept needs further clarification. This study aims to elucidate the concept of reciprocal fit by: (1) investigating the theoretical underpinning of the fit concepts; (2) identifying the conditions of reciprocal fit; and (3) find empirical evidence supporting this reciprocal fit. The originality of this study is in the knowledge contribution of the reciprocal fit concept and the integration of resource-based view and reciprocal determination theory as the underpinning theories supporting the concept.